Real versus ideal: Understanding how coaches gain knowledge - Van Woezik, R. A.; McLaren, C. D.; Côté, J.; Erickson, K.; Law, B.; Lafrance Horning, D.; Callary, B.; Bruner, M. W. (International Sport Coaching Journal, 2022)
In an ever-evolving society, sport coaches are presented with a number of avenues through which they can acquire and refine their coaching knowledge. The purpose of this research was to replicate and extend past research to gain an up-to-date understanding of how coaches are presently gaining knowledge. This was done through a constructive replication using a sequential explanatory mixed-method design. Study 1 included 798 coaches who completed an online questionnaire detailing their use of 16 sources of coaching knowledge. Coaches` top three most used sources were interacting with coaches, learning by doing, and observing others. In contrast, the top three most preferred sources were observing others, interacting with coaches, and having a mentor. To contextualize these findings, Study 2 used a qualitative design in which 14 coaches were interviewed to understand their experiences with different knowledge sources. Five distinct narrative types were identified: recent elite athletes, parent coaches, coach developers, teacher coaches, and experienced coaches. Coaches reported engaging in more social and unstructured learning experiences, and the reasons for their preferences appeared to differ based on lifestyle and perceived barriers. Collectively, these findings highlight how coaches gain knowledge and why they prefer certain sources over others.